Effects of different land use patterns on the stream water quality in Pasoh, Negeri Sembilan, Malaysia - Yusoff, M.K.; Heng, S.S.; Majid, N.M.; Mokhtaruddin, A.M.; Hanum, I.F.; Alias, M.A.; Kobayashi, S. (Center for International Forestry Research, 2001)
The study focused on the effect of land use activities on stream water quality in Pasoh, Negeri Sembilan, Malaysia. The stream originates in Pasoh Forest Reserve, Negeri Sembilan and then flows through four different types of land use: undisturbed forest, swamp, degraded logged-over forest and agriculture. Water quality parameters chosen for the study include pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), suspended solids (SS), ammoniacal-nitrogen (NH3-N), temperature, electrical conductivity (Ec) and turbidity. Stream flow rate was also measured. Computation of water quality status was based on Department of Environment’s (DOE)-Water Quality Index (DOE-WQI) and Harkin’s Index (HI). Relatively higher values of water quality parameters (DO, BOD, COD, NH3-N, SS and turbidity) and lower value of pH were recorded in the agricultural area. Water quality status started to degrade after the stream passed through the swampy area (DOE-WQI = 88.9, HI = 26.0) and its water quality status was slightly degraded (DOE-WQI = 91.7, HI = 24.0) in the logged-over forest. Overall analysis showed that the water quality status within the agricultural area (DOE-WQI = 92.04, HI = 34.0) was significantly degraded. Stream flow rate plays a significant role in maintaining the water quality status through aeration effects. All sections of the stream fall under Class II (high quality) in terms of overall water quality status classification